Differential Intestinal Microbiota Composition Inhibits the Lactobacillus Growth in Rheumatoid Arthritis Patients in Malang, Indonesia. - Mufidah, Mufidah; Suyanto, Eko; Sutanti, Viranda; Meidinna, Hazna Noor; Fatchiyah, Fatchiyah (Graduate School, Universitas Brawijaya, 2020)
Rheumatoid arthritis (RA) is an autoimmune disease that can cause progressive damage to the joints of patients. The number of patients is expected to increase, along with the exact cause of this disease remains unknown. However, there are several risk factors associated with RA, including dysbiosis. The purpose of this study was to characterize the composition of intestinal microbiota in the RA and control groups through fecal analysis and reveal the association of microbiota composition with RA disease in Indonesia, especially Malang. Fecal samples were obtained from RA patients and controls. Fecal analysis was carried out through several stages, namely the calculation of total bacterial colonies, isolation and characterization of anaerobic bacteria, calculation of the Simpson diversity index, and DNA isolation. Analysis of bacterial composition profiles in fecal was carried out using 6 specific primer sets through PCR analysis. The results of the 16S rRNA PCR analysis showed different microbiota compositions between RA patients and controls. The number of Enterococcus bacterial group was lower in the control patients than the RA group, whereas the Lactobacillus bacteria decreased in RA patients. In addition, our study found that the existence of bacterial isolate 11 changed the composition of microbiota in RA patients, and the DNA band only appeared in Universal primers. The diversity of bacterial species can provide symbiotic and pathogenetic effects in RA patients.Keywords: Dysbiosis, intestinal microbiota, PCR, rheumatoid arthritis.